Jack of spades [large type] : a tale of suspense - Oates, Joyce Carol, 1938- (Center Point Large Print, 2015)
"When a venerated mystery writer is accused of plagiarism by a strange woman from his small New Jersey town, his life--and sanity--begins to unravel in the literary thriller"--